Numerical analysis of characteristics of wideband planar disk-slot antenna - Tsaliev, T.A.; Siden, S.V. (Radiotekhnika, 2018)
Electrodynamic descriptions of the co-planar construction of the linear polarization antenna are examined as a combination of a flat conducting screen with a circular opening and circular disk accommodated in the plane of this opening. The disk is connected to the power source by means of a coplanar line and is shifted so that the edges of the circular opening and the disk form a crack of a variable width. The results of numerical modeling of the characteristics of such an antenna in the presence of a dielectric substrate and without it are presented, discussed and compared. It is shown that such a fully co-planar (including power line) antenna design has improved frequency properties, both in agreement with the input and the directional coefficient.